Do lumen-apposing metal stents (LAMS) improve treatment outcomes of walled-off pancreatic necrosis over plastic stents using dual-modality drainage? - Sahar, Nadav; Kozarek, Richard; Kanji, Zaheer S.; Ross, Andrew S.; Gluck, Michael; Gan, S. Ian; Larsen, Michael; Irani, Shayan (Endoscopy International Open, 2017)
Background and study aims Endoscopic ultrasound-guided drainage of symptomatic walled-off pancreatic necrosis (WON) usually has been performed with double pigtail plastic stents (DPS) and more recently, with lumen-apposing metal stents (LAMS). However, LAMS are significantly more expensive and there are no comparative studies with DPS. Accordingly, we compared our experience with combined endoscopic and percutaneous drainage (dual-modality drainage [DMD]) for symptomatic WON using LAMS versus DPS.Patients and methods Patients who underwent DMD of WON between July 2011 and June 2016 using LAMS were compared with a matched group treated with DPS. Technical success, clinical success, need for reintervention and adverse events (AE) were recorded. Results A total of 50 patients (31 males, 25 patients treated with LAMS and 25 patients treated with DPS) were matched for age, sex, computed tomography severity index, and disconnected pancreatic ducts. Technical success was achieved in all patients. Mean days hospitalized post-intervention (14.5 vs. 13.1, P = 0.72), time to resolution of WON (77 days vs. 63 days, P = 0.57) and mean follow-up (207 days vs. 258 days, P = 0.34) were comparable in both groups. AEs were similar in both groups (6 vs. 8, P = 0.53). Patients treated with LAMS had significantly more reinterventions per patient (1.5 vs. 0.72, P = 0.01). Conclusions In treatment of symptomatic WON using DMD, LAMS did not shorten time to percutaneous drain removal and was not associated with fewer AEs.